SISTEM INFORMASI MONITORING AKTIVITAS ANAK BERBASIS WEB DAN MOBILE - Alexander Samuel; Lina Lina; Desi Arisandi (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Before entering elementary school level, children will learn through PAUD (Early Childhood Education). Paud activities are various. Seeing from this PAUD activity, of  course parents need to see and monitor the activities of their children if parents cannot accompany them at school. The information system for monitoring PAUD children’s activities is expected to be able to help parens to see the children’s activities carried out while at school. This system is made using two platforms, namely web-based whose main feature monitoring children’s activities, and mobile-based to view data that has been entered from the web